Effect of intravenous zoledronic acid infusion on electrocardiographic parameters in patients with osteoporosis. Issue 12 (December 2016) - Aktas, I.; Nazikoglu, C.; Kepez, A.; Ozkan, F.; Kaysin, M.; Akpinar, P.; Dogan, Z.; Ileri, C.; Saymaz, S.; Erdogan, O.
Abstract Summary We evaluated the effects of zoledronic acid (ZA) therapy on electrocardiographic (ECG) parameters for the first time in the literature. Measurements were performed on ECGs obtained before and after ZA infusion on the same day as well as 1 month after the infusion. ZA infusion did not have any short- or long-term effect on any parameter that might be associated with the tendency for atrial fibrillation or ventricular arrhythmias. Introduction The aim of the present study was to evaluate the early and late effects of ZA therapy on ECG parameters which might be associated with the tendency for atrial and ventricular arrhythmias. Methods Consecutive patients with osteoporosis who were admitted to our clinic between December 2013 and December 2014 and who were scheduled to receive ZA infusion constituted our study population. Twelve-lead surface ECGs were obtained from all patients before and after ZA infusion on the same day as well as 1 month after the infusion. All ECG parameters were measured and compared with each other for each patient. Results Data of 100 patients were used in the analysis (9 male; 70.5 ± 11.6 years of age). There were no significant differences between repeated measurements regarding pmax, pmin, and p dispersion values. QT max and QT min values were significantly increased after infusion; however, there were no significant changes in QT dispersion, Tp-e interval, and Tp-e dispersion values. Conclusions ZA infusion did not affect P wave dispersion both at the immediate post-infusion period and 1 month after infusion. QT values were significantly increased early after ZA infusion; however, there were no significant differences in parameters reflecting disparity of ventricular recovery times and transmural dispersion of ventricular repolarization. Based on these observations, it may be suggested that ZA infusion did not have any short- or long-term effect on any parameter that might be associated with the tendency for atrial fibrillation or ventricular arrhythmias.